G320(P) Successful conduct of a UK multi-centre emergency department led paediatric clinical trial: lessons from the eclipse trial. (May 2019) - Woolfall, K; Roper, L; Lyttle, MD; Gamble, C; Humphreys, A; Messahel, S; Hickey, H; Appleton, R
Abstract : Aims: Challenges to the success of 'The Emergency treatment with Levetiracetam or Phenytoin in Status Epilepticus in children (EcLiPSE)' trial included: practitioner anxieties about research without prior consent ('deferred consent'), including how parents would react to being informed their child had already been randomised into the trial; inexperience in conducting an Emergency Department led trial in a paediatric neurological emergency; and use of an anti-epileptic medication (Levetiracetam), which was not the standard medication in this clinical setting. This was a nested study within EcLiPSE that aimed to explore parent and practitioner experiences to inform trial recruitment and conduct. Methods: A mixed method study involving interviews, focus groups and questionnaires with EcLiPSE practitioners and questionnaires and interviews with parents of randomised children. Qualitative data were anonymised and analysed thematically. Quantitative data were cleaned and analysed using descriptive statistics and chi-square test for trend. We present key themes identified from data synthesis. Results: One hundred and forty three parents (93 mothers, 39 fathers, 11 missing parent information) of randomised children completed a questionnaire and 30 (25 mothers, 5 fathers) were interviewed. Ten practitioners (4 medical, 6 nursing) were interviewed, 36 (16 medical, 20 nursing) participated in one of six focus groups and 199 (117 medical, 78 nursing, 3 'other') completed a questionnaire in the final phase of EcLiPSE. Practitioners highly valued bespoke site training, a clinically important research question and simple trial design. These factors, alongside recruitment experience and leadership, were found to facilitate practitioner 'buy in', commitment and ultimately, trial success. Parents supported the trial and understood why consent had been sought after treatment had been given. EcLiPSE was completed on time, achieving its recruitment target. Conclusions: Our study provides valuable insight into factors that helped to facilitate successful conduct and recruitment to a challenging emergency department led trial. The results will hopefully facilitate future research in paediatric emergency departments.